PERSEPSI PAMONG ATAS KETERAMPILAN DASAR MENGAJAR MAHASISWA PPL-2 DI SMA ABDI WACANA PONTIANAK - Pekatip, Pekatip; Achmadi, Parijo; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of the study is "Perception of the Civil Teachers on Basic Skills Teaching Students of PPL-2 FKIP Untan in Abdi Wacana Christian High School Pontianak". Sub problem is how the tutor teacher's perception of the skills of PPL-2 students in implementing teaching methods such as; ask, explain, provide reinforcement, conduct variations of teaching, start and end lessons, manage classes, guide small group discussions, teach small groups and individuals. The research method used is descriptive with the form of skinative research. The research data was sourced from the results of the IPKG and interviews with the PPL-2 Student Civil Servant Teachers at Abdi Wacana High School. Based on IPKG, it is known that 3 students have a pretty good category, 5 students with good category, and 2 students with very good categories.Based on the perception of the KDM tutors, it is known that PPL students are good and varied in terms of asking, providing reinforcement, opening and closing learning skills. Whereas in terms of explaining, variation, classroom management,guiding small group discussions skills, and teaching skills in small groups and individuals skills, PPL students are still less skilled and less varied. From the results of the research that has been done, it is suggested that the Civil Service Teachers should guide them more often, supervise PPL students without allowing them to teach themselves more in class. For PPL students, it is suggested that they better prepare themselves while carrying out PPL-2 assignments even though they are temporary teachers, and many learn the techniques needed in the teaching process in the classroomÂ Keywords: Perceptions of Civil Teachers on Basic Teaching SkillsÂ